A modified bismuth oxychloride photocatalyst and preparation method thereof

By preparing a modified bismuth oxychloride photocatalyst, the multi-layer nanosheet structure is formed using materials such as gadolinium salt, bismuth salt and polyvinylpyrrolidone, which solves the problem of low utilization rate of bismuth oxychloride for visible light and realizes the use of organic pollutants efficient degradation and stable catalytic performance.

CN116870935BActive Publication Date: 2024-12-13BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310469096.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2024-12-13
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

The low utilization rate of bismuth oxychloride photocatalysts on visible light has resulted in limited application in the field of photocatalytics, especially in degrading difficult-to-degrade organic pollutants.

Method used

By using gadolinium salt and bismuth salt as raw materials, polyvinylpyrrolidone as structural modifier, and ethylene glycol as soft template agent and solvent, modified chlorine with a micro-sized flower-like structure composed of multi-layer nanosheets was prepared by solvothermal reactions. Bismuth oxide photocatalyst improves its utilization efficiency and catalytic activity on visible light.

Benefits of technology

The modified bismuth oxychloride photocatalyst significantly improves the utilization rate of visible light, enhances photocatalytic activity, and can efficiently degrade organic pollutants in wastewater, such as isothiazolinone, and the preparation method is simple and suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116870935B_ABST
    Figure CN116870935B_ABST
Patent Text Reader

Abstract

The present invention relates to a modified bismuth oxychloride photocatalyst and a preparation method thereof, and belongs to the technical field of photocatalytic materials. The photocatalyst is prepared by a solvothermal reaction using bismuth salt, gadolinium salt and chloride salt as raw materials, polyvinyl pyrrolidone as a structural modifier, and ethylene glycol as a soft template and solvent at the same time; wherein the molar ratio of gadolinium salt to bismuth salt is 4:(0.3-0.4); the molar ratio of chloride salt to bismuth salt is greater than 1:1; the volume ratio of saturated chloride solution to ethylene glycol is (8-12):(40-60); the feed ratio of polyvinyl pyrrolidine to ethylene glycol is (0.8-1.2) g:(40-60) mL; the photocatalyst is a micron-scale flower-like structure composed of multilayer nanosheets, which can reflect and refract visible light multiple times, thereby improving the utilization efficiency of visible light, having a high specific surface area and a large number of active sites, and can efficiently photocatalytically degrade organic pollutants in wastewater under visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified bismuth oxychloride photocatalyst and a preparation method thereof, belonging to the technical field of photocatalytic materials. Background Art

[0002] Photocatalytic technology has high catalytic activity, good stability, low price and environmental friendliness, and occupies an important position in new environmental pollution water treatment technologies. Bismuth oxychloride is widely used due to its low toxicity, easy band gap modification, high economic benefit and strong catalytic activity, but bismuth oxychloride has a low utilization rate of visible light, and photogenerated electrons-holes are easy to recombine. The above shortcomings limit the practical application of bismuth oxychloride in the field of photocatalysis. The utilization of visible light by bismuth oxychloride photocatalyst is poor, and its absorption wavelength is in a narrow range near ultraviolet light (λ<375nm), and the utilization rate of sunlight is low (<5%). Therefore, how to improve the catalytic performance of bismuth oxychloride photocatalyst and use the catalyst to photocatalytically degrade industrial wastewater is a problem to be solved in this field.

[0003] In order to reduce the band gap (Eg=3.5eV) of bismuth oxychloride photocatalyst, slow down the recombination rate of electron-hole pairs, and improve the interface charge transfer efficiency, the bismuth oxychloride photocatalyst can be surface modified. Patent application CN107597150A reports a method for preparing a rare earth element doped and modified hollow microsphere bismuth oxyiodide photocatalyst, but the rare earth element doped and modified hollow microsphere bismuth oxyiodide photocatalyst has a limited specific surface area, thereby limiting the loading content of active components, and the catalyst composed of a single rare earth element and bismuth oxyiodide has a limited utilization rate of light, resulting in the catalyst being able to only degrade the easily degradable organic pollutant rhodamine B under photocatalytic action, but unable to achieve photocatalytic degradation of organic pollutants that are difficult to degrade, such as isothiazolinone. Summary of the invention

[0004] In order to overcome the defects in the prior art, one of the purposes of the present invention is to provide a modified bismuth oxychloride photocatalyst, which has a layered structure, can reflect and refract visible light multiple times, improves the utilization efficiency of visible light, has a high specific surface area, and has a large number of active sites;

[0005] The second object of the present invention is to provide a method for preparing a modified bismuth oxychloride photocatalyst, which has simple synthesis steps, mild reaction conditions and is convenient for mass production.

[0006] To achieve the purpose of the present invention, the following technical solutions are provided.

[0007] A modified bismuth oxychloride photocatalyst, wherein the modified photocatalyst is prepared by a solvothermal reaction using bismuth salt, gadolinium salt and chloride salt as raw materials, polyvinyl pyrrolidone as a structure modifier, and ethylene glycol as both a soft template and a solvent; the photocatalyst is a micrometer-level flower-like structure composed of multilayer nanosheets;

[0008] Wherein, the molar ratio of the gadolinium salt to the bismuth salt is 4:(0.3-0.4);

[0009] The molar ratio of the chloride salt to the bismuth salt is greater than 1:1;

[0010] The volume ratio of the saturated chloride solution to ethylene glycol is (8-12):(40-60);

[0011] The feeding ratio of polyvinyl pyrrolidine and ethylene glycol is (0.8-1.2) g: (40-60) mL.

[0012] Preferably, the bismuth salt is bismuth nitrate or bismuth nitrate pentahydrate; the chloride salt is sodium chloride; and the gadolinium salt is gadolinium nitrate or gadolinium nitrate hexahydrate.

[0013] Preferably, the modified bismuth oxychloride photocatalyst can degrade organic pollutants in wastewater under the irradiation of a visible light source; the organic pollutants are antibiotics, organic dyes or fungicides;

[0014] The mass concentration of organic pollutants in the wastewater is ≤100 mg·L -1 The dosage of the modified bismuth oxychloride photocatalyst is 0.8 g·L -1 ~4g·L -1 Wastewater;

[0015] Further preferably, the organic pollutant is tetracycline, ciprofloxacin, rhodamine B or isothiazolinone.

[0016] A method for preparing the modified bismuth oxychloride photocatalyst of the present invention, the method steps are as follows:

[0017] (1) adding a saturated solution of chloride salt dropwise to a bismuth salt and stirring the mixture to obtain a solution A; then adding a gadolinium salt to the solution A and stirring the mixture to obtain a solution B;

[0018] (2) adding ethylene glycol dropwise to the solution B obtained in step (1), stirring and mixing to obtain a solution C;

[0019] (3) adding polyvinyl pyrrolidone to the solution C obtained in step (2), stirring and mixing to obtain a solution D;

[0020] (4) The solution D obtained in step (3) is transferred to a reaction vessel for a solvothermal reaction. The reaction time is 5.5 h to 6.5 h and the reaction temperature is 155° C. to 165° C. The solid is separated, washed and dried to obtain the modified bismuth oxychloride photocatalyst.

[0021] Preferably, in step (3), the stirring speed is 150 rpm to 200 rpm, and the stirring time is 30 min to 40 min.

[0022] Preferably, in step (4), the solid is separated by centrifugation; and the drying is performed under vacuum at 75° C. to 85° C. for 6 h to 8 h.

[0023] Beneficial Effects

[0024] (1) The present invention provides a modified bismuth oxychloride photocatalyst, which is a polyvinyl pyrrolidone-modified gadolinium-doped bismuth oxychloride composite photocatalyst. The catalyst has stable properties, and gadolinium doping can form active capture centers, thereby playing the role of a capture trap, so that electrons and holes are separated, and the recombination of electron-hole pairs is inhibited, the life of carriers is prolonged, and the photocatalytic activity is enhanced, and the electron-hole pair recombination rate is reduced; Gd 3+ The d orbital of Bi 3+ The f orbitals overlap, causing the conduction band of bismuth oxychloride to widen and shift downward, while its bandgap width becomes narrower, expanding the light response range; metal doping captures photogenerated electrons and holes, inhibits electron-hole recombination, and thus improves photocatalytic activity; in addition, the addition of polyvinyl pyrrolidone makes the synthesized modified bismuth oxychloride photocatalyst material have a multilayer flower-like nanosphere morphology. The photocatalyst has a layered structure and can reflect and refract visible light multiple times, thereby improving the utilization efficiency of visible light. In addition, it has a high specific surface area and a large number of active sites, further improving the ability to capture and activate active substances.

[0025] (2) The present invention provides a modified bismuth oxychloride photocatalyst, which can achieve efficient treatment of organic pollutants in wastewater under the irradiation of visible light; the photocatalyst can degrade organic pollutants in wastewater under mild reaction conditions, simple operation, high degradation efficiency and short time consumption; when the BIT concentration is ≤100 mg·L -1 In the isothiazolinone wastewater, according to 0.8g·L -1 ~4g·L -1 After the photocatalyst is added and treated for 180 minutes, the BIT removal rate can reach more than 80%, showing good photocatalytic performance.

[0026] (3) The present invention provides a method for preparing a modified bismuth oxychloride photocatalyst, wherein the method comprises a saturated solution of an excess chloride salt, a bismuth salt, a gadolinium salt and polyvinyl pyrrolidone through a solvothermal reaction to prepare a modified bismuth oxychloride photocatalyst in one step; using gadolinium salt as a source of doped rare earth metal, polyvinyl pyrrolidone as a structure modifier, and ethylene glycol as both a solvent and a soft template, and strictly controlling the amount of each substance and the solvothermal reaction conditions, a stable multilayer flower-like nanosphere morphology modified bismuth oxychloride photocatalyst is prepared; the method has simple steps, mild reaction conditions, and is convenient for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a scanning electron microscope (SEM) image of the final product described in Example 1;

[0028] Figure 2 The energy dispersive X-ray spectrometer element distribution map (EDX mapping) of the final product described in Example 1;

[0029] Figure 3 X-ray diffraction (XRD) patterns of the final product of Example 1 and the photocatalysts of Comparative Examples 1 to 4;

[0030] Figure 4 The UV-visible spectra of the final product of Example 1 and the photocatalysts of Comparative Examples 1 to 4 are shown;

[0031] Figure 5 The Kubelka-Munk curves of the final product of Example 1 and the photocatalysts of Comparative Examples 1 to 4;

[0032] Figure 6 The photoluminescence spectra (PL) of the final product of Example 1 and the photocatalysts of Comparative Examples 1 to 4 are shown.

[0033] Figure 7 This is a scanning electron microscope (SEM) image of the gadolinium-doped bismuth oxychloride photocatalyst prepared in Comparative Example 2;

[0034] Figure 8 This is a scanning electron microscope (SEM) image of the bismuth oxychloride photocatalyst prepared using ethylene glycol as solvent in Comparative Example 3;

[0035] Fig. 9 This is a scanning electron microscope (SEM) image of the bismuth oxychloride photocatalyst prepared using water as solvent in Comparative Example 4. DETAILED DESCRIPTION

[0036] In order to explain the technical solution and effects of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0037] (1) The X-ray diffraction pattern (XRD) of the photocatalyst was measured using a Nissan instrument Ultima IV and the crystal phase and grain size were analyzed at a scanning speed of 4° / min and a scanning range of 10 to 80°.

[0038] (2) Bandgap calculation: The bandgap is calculated by testing the UV-visible light absorption spectrum of the photocatalyst. The testing instrument is Beijing Puxi General Instrument TU-1901. During the test, first fill the sample stage with barium sulfate for baseline correction and then fill the sample stage with barium sulfate. Weigh 10 mg of the photocatalyst and place it on the surface of the sample stage. After grinding, test.

[0039] (3) Fluorescence spectrum test: The test instrument is FL-7000 fluorescence spectrometer.

[0040] (4) EDS test: EDS uses the OXFORD INSTRUMENTS X-act test, and SEM uses the Germany, Zeiss, SUPRA 55SAPPHIRE test.

[0041] In the following comparative examples and embodiments, the benzisothiazolinone (BIT) degradation test steps are as follows:

[0042] (1) Weigh 40 mg of benzisothiazolinone (BIT), add 100 mL of deionized water and stir to dissolve. After the solution is completely dissolved, put it into a 1 L volumetric flask to make up to the volume, and obtain a BIT concentration of 40 mg / L -1 is the target pollutant solution;

[0043] (2) 50 mL of the target pollutant solution was measured and placed in a beaker, and 0.06 g of the sample was weighed and added to the beaker; the beaker was placed in a photocatalytic box, and after 30 minutes of dark adsorption to reach adsorption equilibrium, the light source (500 W xenon lamp) was turned on to carry out photocatalytic reaction;

[0044] (3) Degrade for 3 hours. After the degradation is completed, turn off the light source and the degradation is complete. Take out the degradation products, measure the degradation products using a UV-visible light photometer, and calculate the degradation efficiency and degradation effect.

[0045] The calculation formula for the degradation rate of benzisothiazolinone (BIT) is η=(C0-C) / C0×100%, where η is the degradation rate, C0 is the initial concentration of benzisothiazolinone in the reactor, and C is the concentration of benzisothiazolinone at different times in the photocatalytic reaction.

[0046] Example 1

[0047] A method for preparing a modified bismuth oxychloride photocatalyst, the method steps are as follows:

[0048] (1) adding 10 mL of saturated sodium chloride solution dropwise to 1.940 g (4 mmol) of bismuth nitrate pentahydrate, and stirring continuously to obtain solution A; then adding 0.158 g (0.35 mmol) of gadolinium nitrate hexahydrate to solution A, stirring and mixing to obtain solution B;

[0049] Wherein, the molar ratio of the gadolinium salt to the bismuth salt is 4:0.35;

[0050] (2) adding 50 mL of ethylene glycol dropwise to the solution B obtained in step (1), stirring and mixing to obtain a solution C;

[0051] The volume ratio of the saturated sodium chloride solution to ethylene glycol is 10:50;

[0052] (3) adding 1.0 g of polyvinyl pyrrolidone to the solution C obtained in step (2), stirring and mixing uniformly at a stirring speed of 150 rpm for 40 min to obtain a solution D;

[0053] The feeding ratio of polyvinyl pyrrolidine and ethylene glycol is 1.0 g:50 mL;

[0054] (4) The solution D obtained in step (3) was transferred to a reactor for solvothermal reaction. The reaction time was 6 h and the reaction temperature was 160° C. The solid was separated by centrifugation and washed with deionized water, and vacuum dried in a vacuum drying oven at 80° C. for 8 h to obtain a final product powder.

[0055] Example 2

[0056] Example 2 is based on Example 1, except that the amount of saturated sodium chloride solution added in step (1) is replaced by "8 mL" from "10 mL", and the feeding ratio of polyvinyl pyrrolidine to ethylene glycol is 1.0 g:50 mL;

[0057] In step (3), "the stirring speed is 150 rpm and the stirring time is 40 min" is replaced with "the stirring speed is 200 rpm and the stirring time is 30 min";

[0058] In step (4), "reaction time is 6 h, reaction temperature is 160° C." is replaced by "reaction temperature is 165° C., reaction time is 5.5 h"; other conditions remain unchanged to obtain the final product powder;

[0059] The volume ratio of the saturated sodium chloride solution to ethylene glycol is 8:50.

[0060] Example 3

[0061] Example 3 is based on Example 1, except that the amount of saturated sodium chloride solution added in step (1) is replaced by "12 mL" from "10 mL", and the volume ratio of the saturated sodium chloride solution to ethylene glycol is 12:50;

[0062] In step (4), "reaction time is 6 h, reaction temperature is 160 ° C" is replaced by "reaction temperature is 155 ° C, reaction time is 6.5 h", "80 ° C vacuum drying 8 h" is replaced by "75 ° C vacuum drying 6 h", and other conditions remain unchanged to obtain the final product powder; other conditions remain unchanged to obtain the final product powder.

[0063] Example 4

[0064] Example 4 Based on Example 1, "0.158 g (0.35 mmol) of nitric acid hexahydrate" in step (1) was replaced by "0.141 g (0.31 mmol)", and other conditions remained unchanged to obtain a final product powder;

[0065] Wherein, the molar ratio of the gadolinium salt to the bismuth salt is 4:0.31.

[0066] Example 5

[0067] Example 5 Based on Example 1, "0.158 g (0.35 mmol) of nitric acid hexahydrate" in step (1) was replaced by "0.174 g (0.39 mmol)", and other conditions remained unchanged to obtain a final product powder;

[0068] Wherein, the molar ratio of the gadolinium salt to the bismuth salt is 4:0.39.

[0069] Example 6

[0070] Example 6 Based on Example 1, the "1.0 g" of polyvinyl pyrrolidone in step (3) was replaced by "0.8 g", and other conditions remained unchanged to obtain a final product powder;

[0071] The feeding ratio of polyvinyl pyrrolidine and ethylene glycol is 0.8 g:50 mL.

[0072] Example 7

[0073] Example 7 Based on Example 1, the "1.0 g" of polyvinyl pyrrolidone in step (3) was replaced by "1.2 g", and other conditions remained unchanged to obtain a final product powder;

[0074] The feeding ratio of polyvinyl pyrrolidine and ethylene glycol is 1.2 g:50 mL.

[0075] Example 8

[0076] Example 8 Based on Example 1, "50 mL of ethylene glycol" in step (2) was replaced by "40 mL of ethylene glycol", and other conditions remained unchanged to obtain a final product powder;

[0077] The volume ratio of the saturated sodium chloride solution to ethylene glycol is 10:40;

[0078] The feeding ratio of polyvinyl pyrrolidine and ethylene glycol is 1.0 g:40 mL.

[0079] Example 9

[0080] Example 9 Based on Example 1, "50 mL of ethylene glycol" in step (2) was replaced by "60 mL of ethylene glycol", and other conditions remained unchanged to obtain a final product powder;

[0081] The volume ratio of the saturated sodium chloride solution to ethylene glycol is 10:60;

[0082] The feeding ratio of polyvinyl pyrrolidine and ethylene glycol is 1.0 g:60 mL.

[0083] Comparative Example 1

[0084] Comparative Example 1: Based on Example 1, the gadolinium nitrate hexahydrate added in step (1) was removed, and other conditions remained unchanged to obtain a polyvinyl pyrrolidone-modified bismuth oxychloride photocatalyst.

[0085] Comparative Example 2

[0086] Comparative Example 2 is based on Example 1, except that the polyvinyl pyrrolidone added in step (3) is removed, and other conditions remain unchanged to obtain a gadolinium-doped bismuth oxychloride photocatalyst.

[0087] Comparative Example 3

[0088] Comparative Example 3 is based on Example 1, except that the gadolinium nitrate hexahydrate added in step (1) and the polyvinyl pyrrolidone added in step (3) are removed, and other conditions remain unchanged, to obtain a bismuth oxychloride photocatalyst using ethylene glycol as a solvent.

[0089] Comparative Example 4

[0090] Comparative Example 4 is based on Comparative Example 3, except that the "ethylene glycol" in step (2) is replaced by "deionized water" while other conditions remain unchanged, to obtain a bismuth oxychloride photocatalyst using deionized water as solvent.

[0091] The final product prepared in Example 1 was characterized by scanning electron microscopy, and the results were as follows: Figure 1As shown, the final product presents a micron-scale flower-like structure composed of multiple layers of nanosheets, and the diameter of the final product is 4.4 to 7.2 μm; the scanning electron microscope characterization structure of the final products prepared in Examples 2 to 9 is similar to that in Example 1, and all present a micron-scale flower-like structure composed of multiple layers of nanosheets; the structure has a large specific surface area and a higher number of active sites, and the concave-convex layered structure can reflect and refract visible light multiple times, thereby improving the utilization efficiency of visible light.

[0092] The scanning electron microscopy characterization results of the gadolinium-doped bismuth oxychloride photocatalyst prepared in Comparative Example 2 are as follows: Figure 7 As shown, it can be seen that without the addition of the structure modifier polyvinyl pyrrolidone, the bismuth oxychloride and bismuth oxychloride generated by the solvothermal method are both nanosheet structures and cannot be assembled into micrometer-scale flower-like structures;

[0093] Comparative Example 3 The scanning electron microscopy characterization results of the bismuth oxychloride photocatalyst prepared using ethylene glycol as solvent are as follows Figure 8 As shown, it can be seen that when only ethylene glycol is used as a soft template and solvent for solvothermal reaction, and no structure modifier polyvinyl pyrrolidone is added, it is also impossible to assemble into a micron-sized flower-like structure; Comparative Example 4 uses deionized water as a solvent, and the scanning electron microscopy characterization results of the bismuth oxychloride photocatalyst prepared by the solvothermal method are shown in Figure 8 As shown, the bismuth oxychloride has a nanosheet structure and cannot be assembled into a micron-sized flower-like structure; and according to the scanning electron microscope characterization results of the bismuth oxychloride photocatalysts prepared in Comparative Examples 3 and 4, it can be seen that the bismuth oxychloride photocatalyst prepared in Example 4 using deionized water as solvent only presents a smooth regular octahedral nanosheet structure, and the diameter of the nanosheet is 1.7 to 3.2 μm; while the bismuth oxychloride nanosheets prepared in Example 3 using ethylene glycol as solvent show a certain degree of agglomeration and assembly, indicating that ethylene glycol only serves as a solvent for solvent heat and also acts as a soft template.

[0094] The final product prepared in Example 1 was subjected to EDS-mapping scanning, and the results were as follows: Figure 2 As shown, it can be seen that Gd, Bi, Cl, and O elements can be detected on the surface of the final product, and the distribution is relatively uniform, indicating that the rare earth element gadolinium is successfully doped into bismuth oxychloride; polyvinyl pyrrolidone is not directly detected in the EDS-maping scan due to its low doping amount. The EDS-maping scan results of Examples 2 to 9 are similar to those of Example 1. The final product prepared in Example 1 was characterized by X-ray photoelectron spectroscopy (XPS), and N characteristic spectral lines were detected in the XPS full spectrum, proving that nitrogen doping was achieved and polyvinyl pyrrolidone was successfully doped into the final product. The XPS full spectra of Examples 2 to 9 are similar to those of Example 1.

[0095] In summary, the final products prepared in Examples 1 to 9 are the modified bismuth oxychloride photocatalysts of the present invention.

[0096] X-ray diffraction (XRD) analysis was performed on the final product prepared in Example 1 and the photocatalysts described in Comparative Examples 1 to 4. The results are as follows: Figure 3 As shown in the figure, it can be seen that the diffraction peaks of the final product prepared in Example 1 and the photocatalysts described in Comparative Examples 1 to 4 are in good agreement with the standard tetragonal phase BiOCl (JCPDS No. 06-0249) and no other impurity phases are detected, indicating that the synthesized material contains bismuth oxychloride and has a high purity; at the same time, compared with the photocatalysts described in Comparative Examples 2 to 4 without the addition of polyvinyl pyrrolidone modification, the heights of the diffraction peaks of the final product of Example 1 and the photocatalyst described in Comparative Example 1 modified with polyvinyl pyrrolidone all decrease to varying degrees, and the half-peak width becomes wider, indicating that the crystal structure of the material undergoes a major change from the nanoscale to the micron scale; the reason is that polyvinyl pyrrolidone contains a five-membered ring side group, and there is a certain steric hindrance to regulate the growth of bismuth oxychloride crystals, and ethylene glycol not only serves as a system solvent but also acts as a soft template. In addition, the diffraction peak intensity corresponding to the (001) and (002) crystal planes is significantly reduced, while the diffraction peak intensity corresponding to the (110) crystal plane is significantly increased. Therefore, the exposed crystal faces of the crystals change greatly, with reduced exposure of the (001) and (002) crystal faces and increased exposure of the (110) crystal face, which is conducive to electron-hole separation and the generation of active free radicals. The XRD characterization results of the final products of Examples 2 to 9 are similar to those of Example 1.

[0097] The photocatalysts prepared in Example 1 and Comparative Examples 1 to 4 were subjected to UV-visible diffuse reflectance spectroscopy (UV-vis-DRS) analysis. The UV-visible spectra of the final product of Example 1 and the photocatalysts of Comparative Examples 1 to 4 are as follows: Figure 4 As shown, the diffraction peaks of the photocatalyst samples prepared in Example 1 and Comparative Examples 1 to 3 are significantly improved in absorption in the visible light range compared with the photocatalyst prepared in Comparative Example 4; the Kubelka-Munk curves of the final product of Example 1 and the photocatalysts of Comparative Examples 1 to 4 are as shown Figure 5 As shown, it can be seen that the photocatalyst prepared in Example 1 (bandgap width 2.93eV) has a relatively low bandgap width compared to the photocatalyst prepared in Comparative Example 4 (bandgap width 3.23eV), indicating that the polyvinyl pyrrolidone modification and the doping of the rare earth element gadolinium successfully changed the band gap structure of bismuth oxychloride and increased the visible light response region of the photocatalyst, which is conducive to the separation of electron-hole pairs and the generation of active species under visible light conditions. The UV-visible diffuse reflectance spectroscopy analysis results of Examples 2 to 9 are similar to those of Example 1.

[0098] The photocatalysts prepared in Example 1 and Comparative Examples 1 to 4 were subjected to photoluminescence spectroscopy (PL) analysis. The results are as follows: Figure 6 As shown in the figure, it can be seen that the PL signal of the polyvinyl pyrrolidone-modified and rare earth metal gadolinium-doped bismuth oxychloride photocatalyst prepared in Example 1 is significantly weakened compared with the bismuth oxychloride prepared in Comparative Example 4, indicating that the recombination rate of photogenerated carriers is effectively reduced.

[0099] The photocatalytic degradation efficiency of benzisothiazolinone (BIT) by the photocatalysts described in Examples 1 to 9 and Comparative Examples 1 to 4 was tested, and the results are shown in Table 1:

[0100] Table 1 Removal rate of benzisothiazolinone (BIT) by the photocatalysts described in Examples 1 to 9 and Comparative Examples 1 to 4

[0101]

[0102]

[0103] It can be seen from Table 1 that the catalyst of the present invention significantly improves the removal rate of organic pollution by photocatalytic degradation through the synergistic effect of PVP, ethylene glycol, gadolinium and bismuth oxychloride.

[0104] Taking the photocatalyst described in Example 1 as a representative, the effects of the amount of the photocatalyst and the photocatalytic treatment time of the present invention on the removal effect of organic pollutants in wastewater were tested. The specific detection steps are as follows:

[0105] (1) 10 portions with a concentration of 40 mg / L -1 Adding different amounts of the photocatalyst described in Example 1 to a wastewater solution containing benzisothiazolinone (BIT) to obtain a mixed solution;

[0106] The dosage of the photocatalyst is 0.4 g·L -1 Wastewater, 0.8 g·L -1 Wastewater, 1.2 g·L -1 Wastewater, 1.6 g·L -1 Wastewater, 2.0 g·L -1 Wastewater, 2.4 g·L -1 Wastewater, 2.8 g·L -1 Wastewater, 3.2 g·L -1 Wastewater, 3.6 g·L -1 Wastewater, 4.0 g·L -1 Wastewater.

[0107] (2) The mixed solution obtained in step (1) is placed in a photocatalytic box of a 200W xenon lamp, the wavelength range of the xenon lamp is 390nm to 780nm, and the mixed solution obtained in step (1) is stirred by magnetic stirring to carry out a photocatalytic oxidation reaction. The stirring speed is 150rpm. Due to the irradiation of the xenon lamp, the temperature of the photocatalytic oxidation reaction will gradually rise. The reaction temperature ranges from about 25°C to 45°C. When the reaction time is 30min, 60min, 120min and 180min, the mixed solution is taken out and filtered to achieve solid-liquid separation, and the filtered solution is taken for detection.

[0108] The detection is to use a UV-8000 ultraviolet-visible spectrophotometer to measure the ultraviolet absorbance of the filtered solution and measure the BIT content at 318nm. The ultraviolet absorbance is used to reflect the removal rate of BIT in reverse osmosis concentrated water by the photocatalyst prepared in Example 1 at different dosages and treatment times. The test results are shown in Table 2:

[0109] Table 2 Removal rate of BIT by the photocatalyst at different dosages and treatment times

[0110]

[0111] As shown in Table 2, during the photocatalytic oxidation degradation process of the polyvinyl pyrrolidone-modified and rare earth element gadolinium-doped bismuth oxychloride photocatalyst prepared in Example 1, the photocatalyst photocatalyzed the oxidation degradation of BIT in the reverse osmosis concentrated water, and the addition amount of the photocatalyst was 0.4 g·L -1 When the wastewater was photocatalytically degraded for 180 min, the removal rate of BIT could only reach 33.5%; the addition amount of the photocatalyst was 2.0 g·L -1 When the photocatalytic degradation amount was 4.0 g·L, the degradation efficiency of BIT was the highest. After 180 min of photocatalytic degradation, the removal rate of BIT was as high as 93.3%. When the amount of photocatalyst added was further increased, the degradation efficiency of BIT gradually decreased. When the amount of photocatalyst added was 4.0 g·L -1 When the wastewater was photocatalytically degraded for 180 min, the removal rate of BIT was 84.9%, and the addition amount of the photocatalyst was 1.6 g·L -1 When the photocatalytic degradation of wastewater was 180 min, the removal rate of BIT was similar; therefore, considering the catalytic effect and economic cost of the photocatalyst, the dosage of the photocatalyst was 0.8 g·L -1 ~4g·L -1 Wastewater; and within the dosage range, the removal rate of BIT by the catalyst will also increase with the increase of photocatalytic treatment time.

[0112] From the test results of the above comparative examples and embodiments, it can be seen that the modified bismuth oxychloride photocatalyst of the present invention has a lower bandgap width, can utilize visible light to a greater extent, and has a lower recombination rate of photogenerated electron-hole pairs, thereby having a stronger photocatalytic activity; the modified bismuth oxychloride photocatalyst can achieve efficient treatment of organic pollutants in industrial wastewater under the irradiation of visible light, and the reaction conditions are mild, the operation is simple, the treatment efficiency is high and the time consumption is short; and the preparation process of the modified bismuth oxychloride photocatalyst of the present invention is simple, the raw materials are easy to obtain, and the cost is low.

[0113] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. Application of a modified bismuth oxychloride photocatalyst in photocatalytic degradation of isothiazolinone, characterized in that: The modified photocatalyst is prepared by solvothermal reaction using bismuth salt, gadolinium salt and chloride salt as raw materials, polyvinyl pyrrolidone as a structural modifier, and ethylene glycol as both a soft template and a solvent; the photocatalyst is a micron-scale flower-like structure composed of multi-layer nanosheets; Wherein, the molar ratio of the bismuth salt to the gadolinium salt is 4:(0.3-0.4); The molar ratio of the chloride salt to the bismuth salt is greater than 1:1; The volume ratio of the saturated chloride solution to ethylene glycol is (8-12):(40-60); The feeding ratio of polyvinyl pyrrolidine and ethylene glycol is (0.8-1.2) g: (40-60) mL.

2. The use of a modified bismuth oxychloride photocatalyst in photocatalytic degradation of isothiazolinone according to claim 1, characterized in that: The bismuth salt is bismuth nitrate or bismuth nitrate pentahydrate; the chloride salt is sodium chloride; and the gadolinium salt is gadolinium nitrate or gadolinium nitrate hexahydrate.

3. Use of a modified bismuth oxychloride photocatalyst in photocatalytic degradation of isothiazolinone according to claim 1 or 2, characterized in that: The modified bismuth oxychloride photocatalyst can degrade isothiazolinone in wastewater under the irradiation of a visible light source; The mass concentration of isothiazolinone in the wastewater is ≤100 mg·L -1 The dosage of the modified bismuth oxychloride photocatalyst is 0.8 g·L -1 ~4g·L -1 Wastewater.

4. Use of a modified bismuth oxychloride photocatalyst in photocatalytic degradation of isothiazolinone according to claim 1 or 2, characterized in that: The modified bismuth oxychloride photocatalyst is prepared by the following method, and the method steps are as follows: (1) adding a saturated solution of chloride salt dropwise to a bismuth salt and stirring the mixture to obtain a solution A; then adding a gadolinium salt to the solution A and stirring the mixture to obtain a solution B; (2) adding ethylene glycol dropwise into solution B, stirring and mixing to obtain solution C; (3) adding polyvinyl pyrrolidone to solution C, stirring and mixing to obtain solution D; (4) Transferring solution D to a reactor for solvothermal reaction, the reaction time is 5.5 h to 6.5 h, the reaction temperature is 155° C. to 165° C., separating the solid, washing and drying, and obtaining the modified bismuth oxychloride photocatalyst.

5. The use of a modified bismuth oxychloride photocatalyst in photocatalytic degradation of isothiazolinone according to claim 4, characterized in that: In step (3), the stirring speed is 150 rpm to 200 rpm, and the stirring time is 30 min to 40 min; in step (4), the solid separation method is centrifugal separation; and the drying condition is vacuum drying at 75° C. to 85° C. for 6 h to 8 h.